Skrining kandidiasis oral pada saliva warga binaan di Lembaga Pemasyarakatan perempuan Kelas II A Sungguminasa - Fadilah, Umi Nur; Hartati; Sunaidi, Yanti (Tropis: Jurnal Riset Teknologi Laboratorium Medis, 2024)
Candida albicans is a normal microflora that lives in the human body, inculding in the oral cavity, skin, nails, respirator tract, and digestive tract. In the oral cavity, changes in the form of Candida albicans from commensel to pathogenic resulting in oral candidiasis are caused by predisposing factors, including disruption of the normal flora of the oral cavity due to long- term use of broad- spectrum antibiotics, excessive use of mouthwash, irritation due to the use of dentures, lack of maintaining oral hygiene, immune disorders due to diseases such as AIDS, Diabetes mellitus. The purpose of this study was to determine the results of oral candidiasis screening on the saliva of assisted citizens at the Sungguminasa Class IIA Women’s Correctional Institution. The samples used were saliva from assisted residents at the Sungguminasa Class IIA Women’s Community Institution. Saliva samples was screened for Candida albicans fungus by examination using the culture method for 3 – 7 days and continued with gram staining. Based on the research conducted, it can be concluded that from 10 (100%) samples obtained 7 (70%) positive samples of Candida albicans with a maximum number of colonies of 65 colonies and at least 2 colonies with an averge colony count of 22.71. While 3 (30%) samples were negative for Candida albicans. The conclusion of the screening results obtained showed that the samples that were examined and obtained positive resutls were said not to be infected with oral candidiasis, but the identified Candida albicans was still classified as normal flora in the oral cavity, this is because the number of colonies in the positive sampel <100 which showed no increase in colonies.